IMPROVEMENT OF DYNAMICS OF CARTRIDGE WORKS FOR FORMING RAIL CONCRETE PRODUCTS - Sivko, V. J.; Yakovenko, V. B.; Mishchuk, E. O. (Техніка будівництва, 2020)
The paper presents the results of experimental studies of the patterns of eigenvalues of cassette installations with and without consideration of the concrete mixture. On the basis of research, an analysis of the most favorable modes of operation of the cassette installation is carried out. The results of numerical calculations of the cassette system by the finite element method taking into account the coefficients of influence are given. The five frequencies and the corresponding forms of their own oscillations have been obtained, the analysis of which has shown that the most feasible from the technological point of view is the third form.